Height Prediction Based On Foot Length among Western UP Population (International Journal of Food and Nutritional Sciences, 2022)
Background: The primary criterion for identifying any specific person is their stature, which provides a critical cue for picking out that person from a crowd. When a body part is missing, the relationship between its measurements and height is employed to match one body component to another.Objectives: The goal of the current work was to develop a regression equation for estimating height from foot length. They discovered a relationship between foot length and height in the western up population.Materials and Methods: This study involved 500 participants from Western Uttar Pradesh (250 men and 250 women), ranging in age from 18 to 25.Results: There was a significant correlation (r) between height and foot length (males' right and left foot lengths is0.73 and 0.72 respectively, and females' right and left foot lengths are.58 and .51, respectively, with a p value less than 0.05. In case of males, the regression equation for height and foot length is Y=72.08+3.04(RFL), and Y=75.97+3.6(LFL).For females, the regression equation is Y=85.62+3.2(RFL), and Y=83.02+3.11(LFL)Conclusion: The current study has revealed a clear correlation between stature and foot length as well as a regression equation. In this investigation, the minimum acceptable error in the assessment of stature and a statistically moderate association between height and foot length were discovered